2021
DOI: 10.1177/20514158211059057
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluating the diagnostic efficacy of PSA as a referral test to detect clinically significant prostate cancer in contemporary MRI-based image-guided biopsy pathways

Abstract: Introduction: Modern image-guided biopsy pathways at diagnostic centres have greatly refined the investigations of men referred with suspected prostate cancer. However, the referral criteria from primary care are still based on historical prostate-specific antigen (PSA) cut-offs and age-referenced thresholds. Here, we tested whether better contemporary pathways and biopsy methods had improved the predictive utility value of PSA referral thresholds. Methods: PSA referral thresholds, age-referenced ranges and PS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…One caveat is that many of these studies were done before pre-biopsy MRI imaging to target biopsies (as in modern pathways) and tumours may have been harder to find in larger prostates. However, a recent study from our own unit has identified that size-cancer relationship remained the same (inverse) in men investigated by MRI-guided biopsies [19].…”
Section: Prostate Cancer and Gland Sizementioning
confidence: 89%
“…One caveat is that many of these studies were done before pre-biopsy MRI imaging to target biopsies (as in modern pathways) and tumours may have been harder to find in larger prostates. However, a recent study from our own unit has identified that size-cancer relationship remained the same (inverse) in men investigated by MRI-guided biopsies [19].…”
Section: Prostate Cancer and Gland Sizementioning
confidence: 89%
“…This indicates that large prostates may be protective of PCa when compared to smaller prostates, which is favorable for the limited wave penetration of MicroUS. This finding is supported by the study of Lophatananon et al, who enrolled 2767 men suspected of PCa and found mean gland volume higher in men with a benign diagnosis (68.1 mL, SD = 35.5, p < 0.0001) compared to any PCa (52.5 mL, SD = 29.0, p < 0.0001) or csPCa (51.9 mL, SD = 30.0, p < 0.0001) diagnosis [48]. However, the same small PCa lesion is easier to be hit by a biopsy needle in a small prostate than in a much larger prostate.…”
Section: High Frequency Micro-ultrasoundmentioning
confidence: 98%
“…Systematic review and meta-analysis studies on transrectal ultrasound and MRI have shown a highly significant negative association between prostate/BPH size and incidence of biopsy-proven PCa; no study was found showing the contrary. 1–3 Since this phenomenon and possible causes are controversially discussed, this should encourage researchers and clinicians to further investigate the dynamic interactions between the different prostatic zones in aging men with growing prostates. A better understanding of the cancer risks in the PZ and TZ could significantly influence future clinical management of both diseases, BPH and PCa alike.…”
mentioning
confidence: 99%